Factors Associated With The Completeness Of Basic Immunization In Children In The Working Area Of Teluk Lubuk Public Health Center - Sari Wahyuni; rusmita; Wilma; ⁠Asri Novianti; Miskiyah; Rohaya (Afiyatun Journal of Health Sciences, 2025)
Background: Complete basic immunization is an important preventive effort to protect children from various infectious diseases. However, the coverage of basic immunization in several regions of Indonesia has not yet reached the national target, including in the working area of Teluk Lubuk Public Health Center. Various factors such as maternal knowledge, attitude, and occupation are suspected to be associated with the completeness of basic immunization. Therefore, this study aims to determine the factors associated with the completeness of basic immunization in children. Objective: To identify the factors associated with the completeness of basic immunization in children in the working area of Teluk Lubuk Public Health Center in 2025. Methods: This study employed a quantitative design with a cross-sectional approach. The study was conducted in February 2025. The population consisted of all mothers with children aged 12–24 months in the working area of Teluk Lubuk Public Health Center. A total of 97 respondents were selected using total sampling technique. Data were analyzed using the chi-square test and odds ratio (OR). Results: A total of 54.6% of children received complete basic immunization. There was a significant relationship between maternal knowledge (p=0.000; OR=3.628) and maternal attitude (p=0.045; OR=2.522) with the completeness of basic immunization. However, maternal occupation was not significantly associated with immunization completeness (p=0.528; OR=0.710). Conclusion: Maternal knowledge and attitude are significantly associated with the completeness of basic immunization in children, while maternal occupation is not. Efforts to enhance health education and promotion by health workers are necessary to increase maternal awareness of the importance of basic immunization.